Influence of Fe2+ doping concentration on the structure and spectroscopic properties of transparent glass-ceramics based on Fe2+:ZnAl2O4 nanocrystals. (December 2020) - Eremeev, K; Dymshits, O; Khubetsov, A; Alekseeva, I; Zapalova, S; Tsenter, M; Zhilin, A.; Basyrova, L; Loiko, P; Popkov, V
Abstract: Zinc aluminosilicate glasses nucleated by titanium dioxide, both undoped and doped with 0.6 and 1.0 wt% FeO were prepared by conventional melt-quenching technique and subsequently converted to glass-ceramics by controlled nucleation and crystallization in the temperature range of 720 – 1200 °C. The glasses and glass-ceramics were characterized by X-ray diffraction, Raman and optical spectroscopy. The addition of FeO speeds up the liquid phase separation of the initial glasses and gahnite (ZnAl2 O4 ), rutile (TiO2 ) and cristobalite (SiO2 ) crystallization. Ferrous ions enter the gahnite crystals leading to a variation of the absorption spectra of glass-ceramics as compared to those of glasses. The glass-ceramics exhibit a broadband (1.5-2.5 μm) absorption due to the 5 E → 5 T2 ( 5 D) transition of Fe 2+ ions in tetrahedral sites in gahnite nanocrystals. They are promising as materials for gain media and saturable absorbers of mid-infrared lasers.